Caregiving strategies in families of children with congenital heart disease: A qualitative study - Zahra Dalir; Zahra-Sadat Manzari; Hossein Kareshki; Abbas Heydari (Wolters Kluwer Medknow Publications, 2021)
Background: The families of children with Congenital Heart Disease (CHD) experience challenges in taking care of their child, which may affect the whole family. Therefore, the families need to manage and organize the caregiving process for the child. In order to help families provide optimized and quality care for their child, it is important to understand how they manage caregiving challenges. This study was conducted with the aim to explore the strategies used by families for managing family caregiving for their child. Materials and Methods: This qualitative study was conducted on families of children with CHD referred to hospitals in Mashhad, Iran. The participants were selected using a purposive sampling method. The data were collected from among 40 eligible participants using in-depth and semi-structured interviews from November 2017 to December 2018. Conventional content analysis was used for data analysis and MAXQDA software for managing the coding process. Results: According to the results, effort to manage caregiving emerged as the main theme, which included the 4 categories of "monitoring the child's health conditions," "organizing family life," "optimizing family life," and "establishing interaction." Conclusions: The families used various strategies to manage caregiving including monitoring of the child's health conditions, organization, and optimization of family life, and effective interaction based on their knowledge, experiences, beliefs, and available sources. The results of the present study can help healthcare professionals and nurses to develop family-centered empowerment programs in order to promote families' abilities to manage family caregiving for a child with CHD.